Povezanost med Fizioterapevtsko ocenjevalno lestvico za bolnike s Parkinsonovo boleznijo in Lestvico za samooceno prizadetosti bolnika - Krizmanič, Tatjana (Rehabilitacija (Ljubljana), 2011)
Background: The aim of the study was to test the usefulness of a newly compiled Physiotherapeutic Assessment Scale for Parkinson's Disease Patients (PASPPD) in clinical practice. We wanted to test its association with the Self-Assessment Parkinson's Disease Disability Scale (SAPDDS). Methods: Twenty-nine Parkinson's disease patients participated. Their mean age was 70 years (range 47-87 years). They all received inpatient treatment at the University Rehabilitation Institute in Ljubljana. All the patients were assessed using PASPPD and they completed the SAPDDS themselves. Association between the two scales was depicted using scatterplot and assessed using Pearson correlation. Agreement between five pairs of items present in both scales was assessed using intraclass correlation (ICC (3,1)). Results: We found high positive correlation between PASPPD and SAPDDS score (r = 0.735, p < 0.001). We found medium agreement between the selected pairs of items (ICC(3,1) values between 0.4 and 0.7, p < 0.05). Conclusion: PASPPD provides data on patient's impairments and disabilities, whereby individual items indicate the recommendations for additional testing and provide guidelines for planning physiotherapy programme.
Keywords: fizioterapija; ocenjevalne lestvice; Parkinsonova bolezen; physiotherapy